2009
DOI: 10.1038/ki.2009.115
|View full text |Cite
|
Sign up to set email alerts
|

A urinary biomarker profile for children with HIV-associated renal diseases

Abstract: Human immunodeficiency virus (HIV)-infected children are at risk of developing several types of renal diseases, including HIV-associated nephropathy (HIVAN), which is usually seen during late stages of infection in children with a high viral load. This disease is defined by the presence of proteinuria associated with mesangial hyperplasia and/or global–focal segmental glomerulosclerosis combined with microcystic transformation of the renal tubules. Because HIVAN can have an insidious clinical onset, renal biop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
40
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 47 publications
1
40
1
Order By: Relevance
“…[47][48][49] In children with HIVAN, the urinary levels of MMP-9 are increased in correlation with the progression of their renal disease. 14,16 Therefore, because MMP-9 facilitates the release of FGF-2, 34 our findings may provide an alternative mechanism by which Tat can regulate the activity of FGF-2 in podocytes.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…[47][48][49] In children with HIVAN, the urinary levels of MMP-9 are increased in correlation with the progression of their renal disease. 14,16 Therefore, because MMP-9 facilitates the release of FGF-2, 34 our findings may provide an alternative mechanism by which Tat can regulate the activity of FGF-2 in podocytes.…”
Section: Discussionmentioning
confidence: 99%
“…51 Thus, differentiated podocytes that are forced to re-enter the cell cycle under the influence of Tat and FGF-2 may be unable to divide and could detach or undergo apoptosis. Considering that FGF-2 is accumulated in the circulation, glomeruli, and urine of children with HIVAN, 13,14,16,17,36 it is tempting to speculate that the podocytes carrying the genetic risk variants that predispose to HIVAN 52,53 may be more sensitive to this pathogenic mechanism. In support of this notion, we found that both Tat and FGF-2 can precipitate the development of HIVAN in HIVTg 26 mice.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations